Gerakan adaptasi pangan lokal “pangan bijak nusantara” mendukung sistem pangan berkelanjutan Indonesia - Marthalia, Lusye; Frimawaty, Evi (Jurnal Inovasi Pangan dan Gizi, 2024)
Food is an important issue in meeting human needs and life, which currently faces many challenges. Background: This paper aims to present the role of the "Pangan Bijak Nusantara" as a form of food advocacy beneficial for food sustainability in Indonesia. Methods: This paper does not employ a rigid methodological framework as it relies solely on literature studies or reviews related to the topic. Finding: The "Pangan Bijak Nusantara" is a campaign aimed at encouraging and accelerating changes towards local, healthy, fair, and sustainable food consumption, production, and distribution patterns. This campaign seeks to encourage the community to consume local, healthy, fair, and sustainable food products. Conclusion: Through this campaign, it is expected that local food systems will be recognized and promoted within society, ultimately creating food resilience and robustness. Novelty/Originality of this article: This paper emphasizes that stakeholders in the food system can play their roles in advancing local food systems by reintroducing food production processes and the various types of archipelagic foods, along with cultural values, social ethics, and environmental preservation. This is because the food system is a complex network.